Fabrication of MoS2/Al-doped ZnO core/shell inverse opal structure for water splitting - See Toh, Gerald Keat Hung (2017)
A photoelectrochemical (PEC) cell undergoes photocatalysis to produce hydrogen (H2) and oxygen (O2) gas. The PEC cell configuration focused in this research is photoanode and metal cathode combination. The photoanode, a semiconductor, works by converting incident photons from the sun in order to create electron-hole pairs. As the photoanode contributes largely to the efficiency of the PEC cell, the selection of the materials used is important. There are multiple advantages and trade-off to each and every material which needs to be tuned and fabricated. A photonic crystal is a suitable structure for water splitting application. It works by the cancellation of a range of wavelength due to its long-range ordered structure. As light enters the crystal, it will reflect and refract off the interfaces creating overlapping light beams within the crystal, which leads to the cancellation of a certain wavelength. Among them, the inverse opal, which is a replicated shell structure of a face-centred-cubic (FCC) opal, offers very high specific surface area and porosity (74% void volume). Besides, the periodical 3D inverse opal can provide an additional photonic bandgap effect to enhance the light–matter interactions by controlling the propagation of light via back reflections, slow photons, and surface resonant modes. As such, the 3D inverse opal structure is expected to be an ideal electrode design for energy conversion applications. One example of a photonic crystal is an inverse opal structure. Through an opal template, an inverse opal structure can be achieved. The opal template, which is made up of polystyrene microsphere, can be tuned by its diameter and concentration. This will alter the properties of the photonic crystal. An inverse opal will then be synthesised through the infiltration of the precursor. Zinc Oxide is the material chosen for inverse opal. However, there is a trade-off for this material and a secondary material will have a layer on top creating a core/shell inverse structure. MoS2 is selected due to its small band gap and its ability to straddle the reduction and oxidation potential of water. Nevertheless, it is hard to synthesise MoS2 precisely in a complex structure. Atomic layer deposition (ALD) would be the ideal method to use. ALD makes use of two precursors to create individual layers of material and purges after the reaction of each precursor on the surface. This makes use of the self-limiting mechanism of ALD. The cycles of pulse and purge need to be optimised to prevent wastage of time and material. Closed flow mode of ALD is preferred due to the complexity of the structure. At each stage, characterisation methods are done as a form of confirmation for the process. Opal diameter of 392nm with 0.2% concentration serves best to synthesise the structure. 392nm corresponds to the enhancement of visible light scattering within the inverse opal structure, while 0.2% provides the best thickness for infiltration of precursors. Further testing of its solar-to-chemical efficiency and other materials can be explored.